A biomass derived porous carbon materials with adjustable interfacial electron transmission dynamics as highly-efficient air cathode for Zn-Air battery. (September 2022) - Zhou, Yunjie; Wu, Jie; Wang, Zhenzhen; Huang, Hui; Liu, Yang; Kang, Zhenhui
Highlights: Biomass-derived high-efficiency ORR catalyst that can be mass-produced. The regulation of pore structure on charge transport was in-depth studied by TPV. C111-900 outperforms 20% Pt/C in the operation of Zn-Air battery. Abstract: Biomass-derived catalysts represent one of the greener alternatives for green catalysis. Oxygen reduction electrocatalysts with high efficiency, low cost and large-scale production are the key to promote the commercialization of new energy technology, such as, metal-air battery. Herein, the cheap and available spirulina was used as the carbon source, and a metal-free and porous carbon catalyst (C111-900) was prepared using dual template and solid reaction strategy. The porous structure also regulates the dynamic process of interface charge transfer, which keeps the fast process part of the charge transfer consistent while accelerating the slow process. As a result, C111-900 performs exceptionally well in alkaline media, achieving close to 20% Pt/C, including the half-wave potential, limiting current density and catalytic selectivity. Additionally, it exhibits higher power density (138.5 mW cm −2 ), specific capacity (766.4 mAh gZn −1 ), energy density (958 Wh kgZn −1 ) and has greater stability under high current discharge conditions than 20% Pt/C in Zn-Air batteries Graphical Abstract: Image, graphical abstract